Comparison of high-performance VLSI adders in the energy-delay space. - Oklobdzija, V.G (IEEE Transactions on VLSI systems)
In this paper, we motivate the concept of comparing very large scale integration adders based on their energy-delay characteristics and present results of our estimation technique. This stems from a need to make appropriate selection at the beginning of the design process. The estimation is quick, not requiring extensive simulation or use of computer-aided design tools, yet sufficiently accurate to provide guidance through various choices in the design process. We demonstrate the accuracy of the method by applying it to examples of high-performance 32- and 64-b adders in 100- and 130-nm CMOS technologies.